Developing a Service Mindset. - Lotardo, Elizabeth; Earle McLeod, Lisa (linkedin.com, 2018)
Keep your customers top of mind—even if you're not in a customer-facing role. Learn how to cultivate a service mindset and connect the dots between your job and customer impact.